Economic impact of latent heat thermal energy storage systems within direct steam generating solar thermal power plants with parabolic troughs. (1st July 2017) - Seitz, M.; Johnson, M.; Hübner, S.
Highlights: Integration of a latent heat thermal energy storage system into a solar direct steam generation power cycle. Parametric study of solar field and storage size for determination of the optimal layout. Evaluation of storage impact on the economic performance of the solar thermal power plant. Economic comparison of new direct steam generation plant layout with state-of-the-art oil plant layout. Abstract: One possible way to further reduce levelized costs of electricity of concentrated solar thermal energy is to directly use water/steam as the primary heat transfer fluid within a concentrated collector field. This so-called direct steam generation offers the opportunity of higher operating temperatures and better exergy efficiency. A technical challenge of the direct steam generation technology compared to oil-driven power cycles is a competitive storage technology for heat transfer fluids with a phase change. Latent heat thermal energy storages are suitable for storing heat at a constant temperature and can be used for direct steam generation power plants. The calculation of the economic impact of an economically optimized thermal energy storage system, based on a latent heat thermal energy storage system with phase change material, is the main focus of the presented work. To reach that goal, a thermal energy storage system for a direct steam generation power plant with parabolic troughs in the solar field was thermally designed to determine the boundary conditions. This paper discusses the economic impact of the designed thermal energy storage system based on the levelized costs of electricity results, provided via a wide parametric study. A state-of-the-art power cycle with a primary and a secondary heat transfer fluid and a two-tank thermal energy storage is used as a benchmark technology for electricity generation with solar thermal energy. The benchmark and direct steam generation systems are compared to each other, based respectively on their annual electricity yields and their levelized costs of electricity at two different sites. A brief comparison of a passive and an active latent heat storage system is included. Finally, specific target costs for the new direct steam generation thermal energy storage system are determined based on the results of the parametric study.